Effect of H2O2-VC degradation on structural characteristics and immunomodulatory activity of larch arabinogalactan - Qi, Huimin; Tang, Shuo; Bian, Bin; Lai, Chenhuan; Chen, Yanan; Ling, Zhe; Yong, Qiang (Frontiers in Bioengineering and Biotechnology, 2024)
The arabinogalactan in the representative softwood biomass of larch was degraded using an environmentally friendly hydrogen peroxide and vitamin C (H2O2-VC) system to improve its immunomodulatory activity. Through the H2O2-VC degradation mechanism, hydroxyl radicals are generated, which then target the hydrogen atoms within polysaccharides, resulting in the breaking of glycosidic bonds. Given the impact of oxidative degradation on polysaccharides, we identified three specific arabinogalactan degradation products distinguished by their arabinosyl side chain compositions. The primary structures of the degradation products were investigated using Fourier-transform infrared spectroscopy and nuclear magnetic resonance spectroscopy. Congo red staining showed that the degradation products were absent in the triple-helix structure. The results of the in vitro immunological experiments indicated that an appropriate reduction in the molar ratio of arabinose to galactose enhanced the immunostimulatory effects on RAW 264.7 cells. In addition, the immunostimulatory pathway mediated by arabinogalactan was explored by toll-like receptor 4 (TLR4) inhibitor (TAK-242) These findings provide novel insights into the understanding of the relationship between the structure of arabinogalactan and its biological activity.